Σχεδιασμός ενός μικρού μεγέθους, κινητού συστήματος Draught μπύρας - Γαβριήλ, Αντρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The topic of my thesis with the title «Design of a small scale mobile Draught beer system» has as its main goal, the design and construction of a prototype Draught beer delivery system complete with a cooling system that will entice the customer to purchase the product. I would like to mention that the design was done using a software called SolidWorks. Firstly, we began with the analysis of how the Draught beer system works and once we fully understand the workings of the system we proceeded with the collection of information about the existing systems available in the market today. Then we went on to assess the wants and needs which are required, and calculated the size and the way it will work and the mechanics which will be used for the construction of this system. Finally, after making a feasibility study the final conclusion was reached.
Keywords: Compressor; Draught beer; Refrigerator; Keg; Βαρελίσια μπύρα; Αμμωνία; Σύστημα ψύξης; Συμπιεστής; Σερπαντίνα